Blade dynamics in combined waves and current. (May 2019) - Lei, Jiarui; Nepf, Heidi
Abstract: Submerged aquatic vegetation (SAV), such as seagrass, is flexible and reconfigures (bends) in response to waves and current. The blade motion and reconfiguration modify the hydrodynamic drag. The modified drag can be described by an effective blade length, l e, which is defined as the length of a rigid blade that results in the same drag as a flexible blade of length l . In many natural settings SAV is exposed to combinations of waves and current. This study derived and used laboratory measurements to validate new predictions of effective blade length for combined waves and current based on a Cauchy number, which describes the ratio of hydrodynamic drag to the restoring force due to rigidity of blade. Force measurements on and digital images of blades exposed to waves with a 2-s period and with a range of wave velocity ( U w ) and current speed ( U c ) were used to estimate the effective blade length. The measurements were also used to validate a numerical simulation of blade motion. Once validated, the simulation was used to expand the investigated parameter space to a wider range of wave conditions, and in particular longer wave periods. For U c < 1 4 U w, the blade motion and hydrodynamic drag were wave-dominated. For U c > 2 U w, the blade motion and hydrodynamic drag were current-dominated. Highlights: A new prediction of drag on a flexible blade in combined wave and current is derived and validated with experiments. The drag on a flexible blade in waves decreases with increasing current magnitude. The limits of wave-dominated and current-dominated drag are defined.